Dpp and immune response pathway factors mediate paracrine induction of senescent cells in Drosophila - Juan Manuel Garcia-Arias; Mireya Ruiz-Losada; Natalia Azpiazu; Ginés Morata (Proceedings of the National Academy of Sciences, 2026)
Transition toward senescence is a cellular response to various forms of stress. This phenomenon is evolutionarily conserved across species, from insects to humans. Senescent cells (SCs) permanently withdraw from the cell cycle and undergo physiological changes, notably the acquisition of a robust secretory activity characterized by the release of numerous molecules, including cytokines, chemokines, and metalloproteinases. Through this program, termed Senescence-Associated Secretory Phenotype, SCs communicate with and influence their microenvironment. In mammalian tissues, the number of SCs increases with age and their accumulation has been proposed to contribute to age-associated pathologies. Studies in vertebrate systems have demonstrated that new SCs can arise through paracrine signaling from preexisting SCs, a process that requires the activity of the Transforming Growth Factor β (TGF-β). We have investigated the occurrence of paracrine recruitment of SCs in the fruitfly Drosophila . Our results show that an initial stress event induces a primary wave of SCs, comprising approximately 10% of the cell population. Subsequently, a second wave of SCs emerges through paracrine signaling from the initial cohort, increasing the overall proportion of SCs to about 24%. The formation of this second wave is mediated by the growth factor Decapentaplegic (Dpp), a Drosophila ortholog of the TGF-β superfamily. Dpp activates a noncanonical signaling route in non-SCs, driving their conversion to a senescent state. This branch of the Dpp pathway engages components of the innate immune response. Collectively, these findings underscore the evolutionary conservation of senescence-associated signaling networks and suggest that paracrine amplification of senescence may play a role in tumorigenesis.